Tissue doppler imaging and Myocardial Performance Index: A Novel approach to assess Right Ventricular Function in Pulmonary Hypertension - Vishwanath Hesarur , Suresh Patted , Sanjay Porwal , Basavaraj Shirol , Payal Kudalkar (Cuestiones de Fisioterapia, 2025)
BackgroundPulmonary hypertension (PH) is a progressive condition characterized by increased pulmonary vascularresistance, leading to right ventricular (RV) dysfunction and poor prognosis. Traditional echocardiographicmeasures often fail to accurately evaluate RV function due to its complex geometry. This study investigatesthe utility of Tissue Doppler Imaging (TDI)-derived Myocardial Performance Index (MPI) as a novel parameterfor assessing RV function in PH patients, comparing it with established echocardiographic measures